Perang Aceh Perlawanan terhadap Kolonialisasi Belanda Aceh War Resistance Against the Colonialization of the Netherlands - Ika Purnamasari; Tappil Rambe; Juni Elfi Br Purba; Dwi Adinda; Muhammad Waldano (Public Service and Governance Journal, 2024)
The Sultanate of Aceh Darussalam is a sovereign kingdom, the Aceh region is famous for its high-value crops throughout the world, Aceh is a large, strong and influential empire in Sumatra, its strategic location makes European countries especially the Netherlands want to control the Aceh Sultanate, but there is public resistance aceh, where the aceh war or sabil war is the war of the aceh people to defend the homeland from the Dutch colony. The Aceh war was motivated by general and special causes that made the Dutch attack Aceh, but the Acehnese people fought against Dutch colonialism and were led by resistance figures such as: Teuku Cut Ali, Teuku Umar, Teuku Cik Di Tiro, and Cut Nyak Dien .this aceh war had an impact on the aceh people and left a legacy in aceh of Dutch colonization.